Joe Floyd Asher With Family And Friends - Watkins, Howard::::::::: (1982)
Front row: Jim Ogie, Louise Asher, Charlie Asher, Wayne Horn, Jamie Asher, Tommy and Jenny Lewis' son; Standing: Jim Mcarty, Jim Mcarty's girlfriend? Robin Asher, Joe Archie Asher, Ralph Everk, Joe Floyd Asher, David Asher, Kathy Abbott Asher, Tommy Lewis, Dwayne Asher, Jenny Lewis, Brian ?